Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Grand Livio Hotel Bali - Ida Ayu Komang Juniasih; Ida Bagus Radendra Suastama; I Gede Artha Ramadiputra (Forum Manajemen, 2023)
Customer satisfaction for staying guests is very important in the hotel accommodation business. Every hotel is required to be able to guarantee customer satisfaction. Customer satisfaction is influenced by many factors including facilities and service quality. This study aims to determine the effect of facilities and service quality partially and simultaneously on customer satisfaction. The research population is Grand Livio Hotel Bali customers and the research sample is 100. The data analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, F Test, t Test and Coefficient of Determination Test. The results showed that facilities had a significant positive effect on customer satisfaction, service quality had a significant positive effect on customer satisfaction and simultaneously facilities and service quality had a significant effect on customer satisfaction. The magnitude of the influence of the variable facilities and service quality on customer satisfaction is 51.3%. Suggestions that can be given by researchers are that the Grand Livio Hotel should add hotel facilities that are still lacking, provide training to employees and provide facilities that suit consumer needs.